Successful qualitative research a practical guide for beginners - Braun, Virginia; Clarke, Victoria (Associate Professor in Sexuality Studies) (SAGE, 2013)
"Successful Qualitative Research: A Practical Guide for Beginners is an accessible, practical textbook. It sidesteps detailed theoretical discussion in favour of providing a comprehensive overview of strategic tips and skills for starting and completing successful qualitative research. Uniquely, the authors provide a 'patterns framework' to qualitative data analysis in this book, also known as 'thematic analysis'. The authors walk you through a basic thematic approach, and compare and contrast this with other approaches. This discussion of commonalities, explaining why and when each method should be used, and in the context of looking at patterns, will provide you with complete confidence for your qualitative research journey. Key features of this textbook: Full of useful tips and strategies for successful qualitative work, for example considering the nervous student not just the beginner student. ; Skills-based, utilising a range of pedagogical features to encourage you to apply particular techniques and learn from your experience ; The authors use the same dataset throughout - reproduced in full (with associated research materials) on the companion website - to help you make comparisons across different analytical approaches. ; A comprehensive suite of student support materials, including practice exam questions, can be found online at www.sagepub.co.uk/braunandclarke. This textbook will be an essential textbook for undergraduates and postgraduates taking a course in qualitative research or using qualitative approaches in a research project."--Publisher's website.